2016
DOI: 10.1523/jneurosci.4263-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Arterial CO 2 Fluctuations Modulate Neuronal Rhythmicity: Implications for MEG and fMRI Studies of Resting-State Networks

Abstract: A fast emerging technique for studying human resting state networks (RSNs) is based on spontaneous temporal fluctuations in neuronal oscillatory power, as measured by magnetoencephalography. However, it has been demonstrated recently that this power is sensitive to modulations in arterial CO2 concentration. Arterial CO2 can be modulated by natural fluctuations in breathing pattern, as might typically occur during the acquisition of an RSN experiment. Here, we demonstrate for the first time the fine-scale depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 50 publications
1
45
0
Order By: Relevance
“…The challenge of distinguishing neural fluctuations from potential respiratory artefacts is made difficult by the fact the respiratory and neural dynamics are unlikely to be independent even without the presence of artefacts. For example, a recent study found that natural fluctuations in end-tidal pCO 2 due to respiration appeared to track oscillatory power in multiple frequency bands as measured by MEG (Driver et al, 2016).…”
Section: Spatial Distribution Of Time Of Day Effectsmentioning
confidence: 99%
“…The challenge of distinguishing neural fluctuations from potential respiratory artefacts is made difficult by the fact the respiratory and neural dynamics are unlikely to be independent even without the presence of artefacts. For example, a recent study found that natural fluctuations in end-tidal pCO 2 due to respiration appeared to track oscillatory power in multiple frequency bands as measured by MEG (Driver et al, 2016).…”
Section: Spatial Distribution Of Time Of Day Effectsmentioning
confidence: 99%
“…Sustained increases in arterial CO 2 is known to suppress neuronal activity (Driver et al, 2016;Hall et al, 2011;Uh et al, 2009) , as measured using electroencephalography (Xu et al, 2011) and magnetoencephalography (Driver et al, 2016;Hall et al, 2011) . This observation spans the delta, alpha, beta and gamma bands.…”
Section: Discussionmentioning
confidence: 99%
“…This observation spans the delta, alpha, beta and gamma bands. Notably, in the resting state, CO 2 fluctuations accounts for 2% of MEG activity variance (r = 0.15) (Driver et al, 2016) . The main mechanism is proposed to be pH, which is inversely correlated with extracellular adenosine concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the "more vascular" networks identified in this study may still fundamentally represent neuronal systems, but are somehow modulated by CO2 levels, whereas the associated "neuronal networks" are not specifically affected. There is emerging evidence that vascular physiology can influence neural activity [34][35][36] , and our lab has demonstrated that end-tidal CO2 changes, during gas inhalation and during resting fluctuations in breathing, can modulate neuronal rhythms as measured using magnetoencephalography (MEG) 37 . It has been further hypothesized that the vasculature may be directly involved in the brain's information processing (the so-called hemo-neural hypothesis 38 ), modulating the excitability of neural circuits via chemical, physical, and thermal mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The BOLD contrast mechanism reflects local levels of deoxygenated hemoglobin, but this is constantly modulated by both direct vasoactive pathways and indirect neurovascular coupling mechanisms. Alternative imaging modalities such as EEG and MEG may provide better direct insight into the neural processes underpinning functional brain networks, however it is not yet fully understood how vascular physiology may manifest in these data 37 or how network activity fluctuations in these different modalities relate back to fMRI signals 45 . In this study, the dual nature of BOLD fMRI contrast, in conjunction with dual stimulus types, facilitates our ability to probe the dual nature of functional brain networks, but perhaps future research should employ multi-modal imaging to best explore these phenomena in greater detail.…”
Section: Discussionmentioning
confidence: 99%